2021
DOI: 10.3389/fphar.2021.797108
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Anti–Vascular Endothelial Growth Factor Monotherapies for Neovascular Age-Related Macular Degeneration: A Mixed Treatment Comparison

Abstract: Background: We aimed to evaluate the comparative efficacy and safety of anti–vascular endothelial growth factor (anti-VEGF) monotherapy to identify its utilization and prioritization in patients with neovascular age-related macular degeneration (nAMD).Methods: Eligible studies included randomized controlled trials comparing the recommended anti-VEGF agents (ranibizumab, bevacizumab, aflibercept, brolucizumab, and conbercept) under various therapeutic regimens. Outcomes of interest included the mean change in b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Nowadays, a few anti-VEGF drugs (e.g., ranibizumab, a monoclonal antibody fragment targeting VEGF-A) have been used in clinical settings to treat RNV, which is most widely used for the treatment of RNV, approved by the U.S. Food and Drug Administration (FDA). Many investigations have demonstrated that the effects of ranibizumab as an up-and-coming RNV treatment are superior to laser treatment with fewer complications . However, ranibizumab has a short half-life (approximate 7 days on average), and sometimes, to achieve a certain therapeutic effect, repeated and frequent intravitreal injections are required, leading to a higher rate of complications such as subconjunctival hemorrhage, increased intraocular pressure, vision-threatening endophthalmitis, and retinal detachment. A variety of complications and increased costs lead to decreased patient compliance, and treatment is often interrupted.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, a few anti-VEGF drugs (e.g., ranibizumab, a monoclonal antibody fragment targeting VEGF-A) have been used in clinical settings to treat RNV, which is most widely used for the treatment of RNV, approved by the U.S. Food and Drug Administration (FDA). Many investigations have demonstrated that the effects of ranibizumab as an up-and-coming RNV treatment are superior to laser treatment with fewer complications . However, ranibizumab has a short half-life (approximate 7 days on average), and sometimes, to achieve a certain therapeutic effect, repeated and frequent intravitreal injections are required, leading to a higher rate of complications such as subconjunctival hemorrhage, increased intraocular pressure, vision-threatening endophthalmitis, and retinal detachment. A variety of complications and increased costs lead to decreased patient compliance, and treatment is often interrupted.…”
Section: Introductionmentioning
confidence: 99%
“…2013;ClinicalTrials.gov, 2015;ClinicalTrials.gov, 2016;ClinicalTrials.gov, 2017;ClinicalTrials.gov, 2020;ClinicalTrials.gov, 2021). Two large studies, HAWK and HARRIER, demonstrated non-inferiority of brolucizumab and an overall safety profile similar to that of aflibercept (Zhang et al, 2021). However, given the different control drugs, dosages, and administration durations of the aforementioned randomized controlled trials, a comprehensive meta-analysis was valuable to evaluate the subtle differences between efficacy and safety of brolucizumab and other anti-VEGF drugs.…”
Section: Introductionmentioning
confidence: 99%
“…These drugs function by inhibiting the activity of VEGF, a pivotal factor in angiogenesis and vascular permeability, thereby reducing macular edema and enhancing visual acuity for patients with these conditions [ 35 , 38 , 37 ]. Research studies indicate that the efficacy of anti-VEGF drugs varies based on the specific drug, dosage, and therapeutic strategy employed [ 35 , 39 ]. For instance, aflibercept has demonstrated greater blocking potency than ranibizumab or bevacizumab [ 35 ].…”
Section: Reviewmentioning
confidence: 99%
“…Despite these findings, controversies persist regarding the ideal drug and optimum therapeutic strategy. Challenges arise in acquiring comparative efficacy and safety profiles from current trials due to many therapeutic regimens involving anti-VEGF therapy, encompassing different drugs, dosages, and therapeutic approaches [ 39 ]. While anti-VEGF therapies effectively address various ocular conditions, the varying efficacy and safety profiles of different drugs, dosages, and therapeutic strategies highlight the need for further research to determine the optimal treatment approach tailored to individual patients.…”
Section: Reviewmentioning
confidence: 99%